Desulfurization of model oil using imidazolium-based ionic liquids - Wan Mohd Syazwan, Wan Abdullah (2013)
Now a day, because of the dramatic environmental impact of sulfur oxides contained in engines emissions, sulfur content specification in fuels are becoming more and more stringent worldwide. In the petroleum refining industry, hydrodesulfurization (HDS) is the conventional process to reduce the sulfur levels of the fuels. However, HDS is cost consuming, besides requiring high temperature and high hydrogen pressure in order to eliminate the aliphatic and alicyclic sulfur compounds. Refractory sulfur compounds such as dibenzothiophene (DBT), methyl dibenzothiophene and 4, 6-methyl dibenzothiophene are less reactive to this process. Due to this reason, alternative sulfur removal techniques are being explored. In the past years, due to its unique properties both as extractant and also as catalyst, ionic liquids have gained increasing interest. 1-ethyl-3-methylimidazolium tetrafluoroborate [EMIM][BF4], has been study in this work. These ionic liquids were characterized using Fourier Transform Infrared spectroscopy (FTIR). The ionic liquids were then screened for sulfur removal from model oil (dodecane). The sulfur containing compound used in preparing the model oil, were DBT with different concentration, 250ppm, 500ppm, 750ppm, 1000ppm, and 2000ppm. In 2000ppm of DBT, contain of 348.04ppm of sulphur. The mixture was heated in the water bath at 30 ºC with a 185 rpm stirring for 30 minutes. The mass ratio of ILs to model oil was 1:1, 1:2, and 1:5. To analyze the model oil that contain of ILs by using High-Performance Liquid Chromatography (HPLC). From this experiment, it show that the higher efficiency of removal sulphur by using 1:1 volume ratio at 750ppm of DBT which is 56% removal...